Functional Analysis of Split Airport Business Processes - Slavko Roguljić; Stanislav Pavlin; Sanja Steiner (Promet (Zagreb), 2005)
Optimisation of business processes represents the basis ofimproving the competitiveness of the Ailport as a service pro·vider. This directly implies not only the analysis and creation ofthe model of current organisation and technological processesbut also the necessity to measure these processes in order to reorganiseand improve them. Consequently, the Split AitportAuthority considers the functional analysis of its business processesas one of the major issues. Since in April2002 the analysisand modelling were completed in all the organisational unitsof handling setvice and cargo department organisational structures,both of the organisational structure of these services, aswell as of processes of aircraft, passenger, baggage and cargohandling, this paper will analyse the implementation of ARISComputer System at Split Airport Ground Handling Process.